Optimization of Operating Conditions of Essential Oil Extraction of Vietnamese Pomelo (Citrus grandis L.) Peels by Hydrodistillation Process - Dao, Tan Phat; Cam Quyen, Ngo Thi; Tran, Thien Hien; Thinh, Pham Van; Long, Pham Quoc; Toan, Tran Quoc; Nguyen, Ngoc Hoi; Hoang Vo, Do Minh; Le, Xuan Tien; Yen Trung, Le Nguyen; Nguyen, Thi Thuong; Yen Nhi, Tran Thi; et al. (Asian Journal of Chemistry, 2019)
This study attempted the optimization of the extraction process involving essential oils from Vietnamese pomelo fruits. Three influential parameters including ratio of water and material, extraction time, and temperature were assumed to be impactful to the oil yield and were investigated by establishing a statistical model. A central composite design was adopted to generate dataset required for estimation of the model. Analysis of variance was used to calculate model significance. The results showed that optimum yield of pomelo oil is 4.46 % (v/w) corresponding to water ratio of 507 mL water to 100 g sample, temperature at 119.29 ºC and distillation time of 113.68 min. Predicted values proposed by the Design Expert 11 software well-agreed with the empirical data, suggesting the excellent predictability of the proposed models. In addition, the essential oil obtained under optimal conditions was analyzed by gas chromatography-mass spectrometry. The results indicated that D-limonene is the main component (97.318 %) of essential oil.